Assessment of surface phytoplankton in whale shark (Rhincodon typus) aggregation areas off Sogod Bay, Southern Leyte, Philippines during whale shark season of November 2017 to February 2018 - Jomadiao, Coleen Gail Yap (2022)
This study determined the phytoplankton community composition and diversity in the whale shark aggregation areas off Sogod Bay, Southern Leyte, from November 2017 to February 2018. Three stations were identified as whale shark aggregation areas and one station had no records of whale shark sightings. Physico-chemical parameters (temperature, pH, salinity, depth, turbidity, water current, and light intensity) were measured in situ. The phosphate, nitrate, and chlorophyll-a were analyzed in the lab.